Layered Double Hydroxide Nanosheets Incorporated Hierarchical Hydrogen Bonding Polymer Networks for Transparent and Fire-Proof Ceramizable Coatings - Guo, Bifan; He, Yimin; Chen, Yongming; Yang, Tianci; Peng, Chaohua; Luo, Weiang; Zeng, Birong; Xu, Yiting; Dai, Lizong (Nano-Micro Letters, 2025)
In recent decades, annual urban fire incidents, including those involving ancient wooden buildings burned, transportation, and solar panels, have increased, leading to significant loss of human life and property. Addressing this issue without altering the surface morphology or interfering with optical behavior of flammable materials poses a substantial challenge. Herein, we present a transparent, low thickness, ceramifiable nanosystem coating composed of a highly adhesive base (poly(SSS1-co-HEMA1)), nanoscale layered double hydroxide sheets as ceramic precursors, and supramolecular melamine di-borate as an accelerator. We demonstrate that this hybrid coating can transform into a porous, fire-resistant protective layer with a highly thermostable vitreous phase upon exposure to flame/heat source. A nanosystem coating of just ~ 100 μm thickness can significantly increase the limiting oxygen index of wood (Pine) to 37.3%, dramatically reduce total heat release by 78.6%, and maintain low smoke toxicity (CITG = 0.016). Detailed molecular force analysis, combined with a comprehensive examination of the underlying flame-retardant mechanisms, underscores the effectiveness of this coating. This work offers a strategy for creating efficient, environmentally friendly coatings with fire safety applications across various industries. Highlights: 1 A transparent and ceramizable coating was developed by incorporating nano-layered double hydroxide nanosheets into hierarchical hydrogen bonding polymer networks. 2 The resulting coating composites demonstrated excellent high-temperature stability and fire resistance, effectively withstanding the direct exposure to a butane flame (~ 1100 °C) in air atmosphere. 3 The mechanisms behind the flame-retardant behavior and ceramicization behaviors were thoroughly investigated and explained.